A quaint & curious volume : essays in honor of John J. Dobbins - Rogers, Dylan Kelby; Weiss, Claire; Dobbins, John Joseph, 1946- (Archaeopress Archaeology, 2021)
Contributions in honour of John J. Dobbins, Professor of Roman Art and Archaeology at the University of Virginia, offers new readings of archaeological data and art, illustrating the impact that one professor can have on the wider field of Roman art and archaeology through the continuing work of his students.